Decreases in Circulating Concentrations of Long-Chain Acylcarnitines and Free Fatty Acids During the Glucose Tolerance Test Represent Tissue-Specific Insulin Sensitivity - Makarova, Elina; Makrecka-Kuka, Marina; Vilks, Karlis; Volska, Kristine; Sevostjanovs, Eduards; Grinberga, Solveiga; Zarkova-Malkova, Olga; Dambrova, Maija; Liepinsh, Edgars (Frontiers in Endocrinology, 2019)
Background. Insulin plays a pivotal role in the regulation of both carbohydrate and lipid intermediate turnover and metabolism. In the transition from a fasted to fed state, insulin action inhibits lipolysis in adipocytes and acylcarnitine synthesis in the muscles and heart. The aim of this study was to measure free fatty acid (FFA) and acylcarnitine levels during the glucose tolerance test as indicators of tissue-specific insulin resistance. Results. Insulin release in response to glucose administration decreased both FFA and long-chain acylcarnitine levels in plasma in healthy control animals by 30% (120 min). The glucose tolerance test and [3H]-deoxy-D-glucose uptake in tissues revealed that high fat diet-induced lipid overload in C57bl/6N mice evoked only adipose tissue insulin resistance, and plasma levels of FFAs did not decrease after glucose administration. In comparison, db/db mice developed type 2 diabetes with severely impaired insulin sensitivity and up to 70% lower glucose uptake in both adipose tissues and muscles (skeletal muscle and heart), and both plasma concentrations of FFAs and long-chain acylcarnitines did not decrease in response to glucose administration. Conclusions. These results link impaired adipose tissue insulin sensitivity with continuous FFA release in the transition from a fasted to postprandial state, while a blunted decrease in long-chain acylcarnitine levels is associated with muscle and heart insulin resistance.